Fertility perspectives and priorities among male adolescents and young adults in cancer survivorship. Issue 7 (14th March 2018) - Nahata, Leena; Caltabellotta, Nicole M.; Yeager, Nicholas D.; Lehmann, Vicky; Whiteside, Stacy L.; O'Brien, Sarah H.; Quinn, Gwendolyn P.; Gerhardt, Cynthia A.
Abstract: Infertility is a common and distressing late effect of cancer treatment among male survivors. Investigators examined desire for parenthood, prioritization of fertility compared to other life goals, and reports of fertility‐related discussions among a cohort of male adolescent and young adult survivors. Eighty percent desired a biological child, yet only 31% ranked having a child among their "top 3" life goals. Only 40% reported fertility‐related discussions with their health care providers in survivorship. Given the importance of biological children among this cohort, future guidelines should encourage a more proactive approach to providing fertility counseling and offering testing, to mitigate distress and prevent unplanned pregnancies.